Firm Size and Financial Performance: Intermediate Effects of Indebtedness. Issue 4 (1st March 2016) - Lopez‐Valeiras, Ernesto; Gomez‐Conde, Jacobo; Fernandez‐Rodriguez, Teresa
ABSTRACT: This paper offers a new perspective for the agricultural economics literature on the relationship between firm size and financial performance. We contribute to the literature by exploring the role of indebtedness in this relationship. Using archival data collected from 83 companies belonging to livestock industries, the empirical findings confirm the hypothesis that indebtedness leverages the effect of size on financial performance. That is to say, indebtedness can enhance the realization of the potential benefits of a larger organizational size. Contrary to expectations, these results reveal that the relationship between size and financial performance is negatively mediated by indebtedness. [EconLit citations: D23; M00; Q13].